New and developing therapies for atopic dermatitis - Tamar Hajar; João Renato Vianna Gontijo; Jon M. Hanifin (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Atopic dermatitis is a common inflammatory skin disease. New understanding in disease pathogenesis has led to a considerable number of promising new drugs in development. New topical agents can be especially helpful for children, providing an alternative to the need for chronic topical corticosteroid use. While many patients with mild or moderate disease can be managed with topical treatments, there are unmet needs for recalcitrant and severe cases. New and developing therapies hold promise for real advances in management of this complex disease.